Examination of Ugandan Educators’ Cultural Preferences when Teaching Agriculture: A Q Methodological Study - Rebekah McCarty; Shannon Norris-Parish; Don Edgar; Lacey Roberts-Hill; Jeff Witte (Journal of International Agricultural and Extension Education, 2024)
Increasing human capital is a critical challenge of developmental aid. Secondary education is known to be the single greatest contributor to agricultural productivity in developing countries. Ultimately, as technology advances, researchers and curriculum designers must investigate variables influencing the successful transmission of agricultural information or the gap will widen. We used framing theory to examine the impact of culture on the adoption of educational resources in a developing nation. The purpose of this study was to investigate the cultural preferences of educators in Uganda when engaging with educational materials created by individuals from a developed nation. We used Q methodology to identify the cultural preferences of individuals from Uganda when engaging with Field of Hope’s agricultural education teacher resources. Six dominant viewpoints emerged—philosophers, visionaries, harmonists, humanitarians, expressive symbolists, and traditionalists. These findings support previous studies that described culture as an individualized experience, even among individuals who shared close organizational and regional affiliations. Considering the role of framing in culture, the successful mobilization of educational resources is highly dependent on resources designed in the target audience’s cultural context. For curriculum designers and practitioners, we recommend conducting a cultural analysis when designing materials for classroom instruction, especially if the resources are designed for a different cultural setting. Recommendations for educators include implementing an increased awareness of cultural differences in the classroom, as well as making a greater effort to integrate regional culture into routine instruction. Future research should explore the impact of culture on the adoption of agricultural practices in developing nations.
Keywords: agricultural education; culture; curriculum development; Q methodology; Uganda